Radio Broadcasting with Artificial Intelligence: A Case Study on Radio Mustang Jakarta - Harliantara, Harliantara; Sompie, Denny Jan; Sutika, I Made (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
This research analyses how the use of Artificial Intelligence (AI) in radio broadcasting by Radio Mustang Jakarta can change the landscape of the broadcasting industry. Through qualitative research, this case study examined radio broadcasting technology development and AI-based innovation in radio programmes. Data was collected through interviews, documentation, and literature studies with triangulation in the data processing. The results revealed that radio is strongly committed to keeping up with advances in information and communication technology. AI in the broadcasting industry can improve the quality and efficiency of broadcasts. In addition, AI technology can revolutionise the broadcasting industry by introducing an AI broadcaster named Aimee through an innovative production process.